SILA STUDIO PROMOTES CERAMICS ART – AN ATTRACTION TO FOREIGNERS - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, August 2015 – Stepping into this studio for the first time has already stirred feelings of being in a rural setting, what more with the studio being within a house almost a centuryold, located at Kampung Jalan Baru, Balik Pulau, Penang.